1999
DOI: 10.1097/00006123-199912000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Zygomatic-Transmandibular Approach for Giant Tumors of the Infratemporal Fossa and Parapharyngeal Space

Abstract: The zygomatic-transmandibular approach allows resection of giant lesions in the middle cranial base, when they are invading the infratemporal fossa and parapharyngeal space, with a low morbidity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 72 publications
0
26
0
5
Order By: Relevance
“…Many series in the literature have reported tumors of the infratemporal fossa that involve the lateral cranial base, posterior fossa, and clivus (8,9,15). The patients in our series with infratemporal fossa lesions were more anteriorly based with involvement of the maxillary sinus, anterior cranial base complex, and orbit.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Many series in the literature have reported tumors of the infratemporal fossa that involve the lateral cranial base, posterior fossa, and clivus (8,9,15). The patients in our series with infratemporal fossa lesions were more anteriorly based with involvement of the maxillary sinus, anterior cranial base complex, and orbit.…”
Section: Discussionmentioning
confidence: 53%
“…It has been suggested that 2.5 cm is the smallest size at which a tumor may become symptomatic (16). Guinto et al (9) reported a series in which the median tumoral diameter was 8 cm at presentation. Some of most common tumors operated in the infratemporal fossa are benign angiofibromas, sphenoid-wing meningiomas, and trigeminal schwannomas, all of which may be cured with gross total resection (8,9,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are numerous surgical approaches, indicating the difficulty of access, accentuated by the communications with the neighboring regions. The main obstacles approaching the infratemporal fossa are the zygomatic arch, the parotid gland, the facial nerve and the ascending ramus of the mandible [11]. Thus for our case, a modified surgical approach was performed with a zygomatic arch access osteotomy and coronoidotomy to excise the tumor mass from the infratemporal fossa.…”
Section: Discussionmentioning
confidence: 99%